Hyporheic invertebrate assemblages at reach scale in a Neotropical stream in Brazil - Mugnai,R. (2015)
Abstract In the Neotropical Region, information concerning hyporheic communities is virtually non-existent. We carried out a sampling survey in the hyporheic zone of the Tijuca River, in the Tijuca National Park, located in the urban area of the city of Rio de Janeiro. Biological samples from the hyporheic zone were collected in three different stream reaches, in June 2012. The main objectives were: 1) to describe the structure of invertebrate assemblages in the hyporheic zone of a neotropical stream; 2) to apply a reach-scale approach in order to investigate spatial patterns of the hyporheic assemblages in relation to hydrology, depth and microhabitat typology. A total of 1460 individuals were collected and identified in 31 taxa belonging to Nematoda, Annelida, Crustacea, Hydrachnidia and Insecta. The class Insecta dominated the upper layer of the hyporheic zone. Copepods were the most abundant taxon among crustaceans and occurred mostly in the upwelling areas of the reaches. The results of this study represent one of the few contributions so far about hyporheic invertebrate assemblages of the Neotropical Region.